Leveraging artificial intelligence (AI) for Stress management in peak athletic performance: an integrative review (2025)
Athletes often experience stressors that can impede their performance and well-being. Lack of coping resource or poorly regulated stress can undermine physical output, decision making and well-being. Effective stress management is crucial for achieving peak performance. This paper synthesize evidence on stress management strategies in sports psychology as well as AI powered stress management strategies using an integrative approach. The findings are presented narratively and organised into emerging themes. These strategies are categorized into cognitive-behavioural strategies, mindfulness-based strategies, relaxation strategies, biofeedback and technology-based and social support, and team-based strategies. AI powered stress management strategies were classified in the study as; AI powered wearable monitoring, virtual therapy and chatbot counseling, predictive analytics for stress forecasting, AI guided biofeedback training, AI enhanced injury and recovery support, AI supported cognitive behavior training, and integration of AI with human support systems. The following benefits are derived from the integration of AI in stress management for athletes; Improved performance, enhanced well-being, continuous and objective stress monitoring, all round support for athletes, Injury prevention, early detection and intervention, personalized training and recovery, confidentiality and stigma reduction. Advances in AI for stress management should focus on refining AI-powered injury prevention models, improving biometric sensing capabilities, advancing edge AI for realtime data processing, and integrating wearables sweat analysis to provide feedback, among others. This paper recommends that multimodal, specific interventions should be integrated into regular athletic training, warm-up and recovery process of athletes in order to attain peak performance and enhance overall well-being. Also that a hybrid approach adopted by sport psychologist integrating AI to support stress management among athletes will lead to a faster and positive outcome in stress management.